Tracing Sydenham's chorea: historical documents from a British paediatric hospital. Issue 5 (25th April 2005) - Martino, D; Tanner, A; Defazio, G; Church, A J; Bhatia, K P; Giovannoni, G; Dale, R C
Abstract : Sydenham's chorea (SC) became a well defined nosological entity only during the second half of the nineteenth century. Such progress was promoted by the availability of large clinical series provided by newly founded paediatric hospitals. This paper analyses the demographic and clinical features of patients with chorea admitted to the first British paediatric hospital (the Hospital for Sick Children, Great Ormond Street, London) between 1852 and 1936. The seasonal and demographic characteristics of SC during this time appear strikingly similar to those observed today, and witness the introduction of modern "statistically averaging" techniques in the approach to complex paediatric syndromes. Great Ormond Street (GOS) hospital case notes provide detailed descriptions of the "typical cases" of SC, and show that British physicians working in the early age of paediatric hospitals succeeded in recognising the most distinctive clinical features of this fascinating condition.